The Eye in the Pre-Islamic Poetry (Amythological study) - Dua’ Hisham Baker Shtayyeh (My University, 2014)
This research revolves around the legend of the eye in the pre-Islamic poetry. This Poetry is stated in an introduction, three chapters, and conclusion. I have talked in the introduction about the reasons of why I have specifically chosen this study, the goal, and the approach I followed and benefited from it. The first chapter is in one study titled: The Legend of the eye in language and thought. In the study, the meanings of the eye were linked according to its mythical origins in the Arab dictionaries. This study is origin and never been addressed by researchers before because it illustrates the origins the eye connotations and it links it to religion and myth and return it all to Annana / Ishtar. In the second chapter, I introduced the myth of human eye in the pre-Islamic poetry through the crying of poets on the ruins. Also, I have mentioned in the second chapter the presence of the eye and shedding tears on the ruins and I divided it into four sections. The first section talks about poets crying on the ruins standing on it and evoking women before shedding tears and the impact of famine and ruins leading to the wailing asking for water and watering the earth to revive the ruins and tombs and this is all revolves around Anana / Ishtar the Goddess of fertility and life. The second section attributes ruins to women (women’s name) and the symbols of those names in language and its relation to Goddess Annana. The third section addresses the impact of women absence on ruins and turning life in to wilderness if absent because she is sacred and represents life and the revival of people. In the last fourth section, I mentioned how the earth cries due to the absence of God. Poet crying on women is equivalent to Ishtar, the Goddess of fertility. Women in such poets were not created by blood and flesh because such crying was offered by the poets in order to get closer to the woman, the Goddess of fertility. The third chapter in the poem entitled as the legend of eye of animals and the natural phenomena in the pre-Islamic poetry. I have divided the third chapter in to four sections. The first section was entitled as eye, lightening, and rain. I have mentioned in this section the relation of the cloud and the rain in the eye Annana/ Ishtar. Ishtar is the only one who can take down the rain and watering the bare ground. In the second section, I mentioned the eye and the brutal cow combined with Hurs and Hat-Hur. The character of Hur may be taken from God Horus, Goddess of Time, or Hat-Hur taken from the cow head and linking them to Hur eyes in paradise. In the third section, I addressed the eye and blue dove and the crying of doves on its son. The last fourth section is entitled as the eye and the son by establishing a close relationship between the woman and the sun. Some poets sees the journey of the woman in the image of the sun in its journey, and the absence of the absence of the sun represents the stealing of Ra’s eye and the appearance of the sun means the eye has been recovered. I finished my research including the most important findings in the study and following it with a list of resources and references arranged by alphabets.

يدور هذا البحث حول العين في الشعر الجاهلي إذ جاء في مقدمة وثلاثة فصول وخاتمة. تحدثت في المقدمة عن أسباب اختياري لهذه الدراسة، والهدف الذي أردتُ إثباته من خلالها، والمنهج الذي اتبعته واستفدتُ منه، وهذه الدراسة لم يتطرق إليها أحد؛ لأنها تبحث عن أصول دلالات العين، وارتباطها بالدين والأسطورة وعودتها جميعها إلى عنانا / عشتار. جاء عنوان الفصل الأول: أسطورة العين في اللغة والفكر، فقد ربطتُ معاني العين الواردة في المعاجم العربية بأصولها الأسطورية. أما الفصل الثاني فعرضت فيه أسطورة العين البشرية في الشِّعر الجاهليّ، وذلك من خلال بكاء الشعراء على الأطلال، وتناولت فيه حضور العين وذرف الدموع على الأطلال، إذ قسمته إلى أربعة مباحث، عرضت في الأول منها: بكاء الشعراء على الأطلال، ووقوفهم عليها، واستحضار المرأة قبل ذرف الدموع، وأثر الجدب والخراب المؤدي إلى النواح؛ لطلب الماء، واستسقاء الأرض لإحياء الأطلال والقبور، وكل ذلك يدور حول عشتار / عنانا إلهة الخصب والحياة، وتناولتُ في المبحث الثاني نسبة الأطلال إلى المرأة (أسماء النساء) ورموز هذه الأسماء في اللغة وارتباطها بالإلهة عنانا، وفي المبحث الثالث تطرقتُ إلى أثر غياب المرأة عن الطلل، وتحويل الأرض إلى قفار حال غيابها؛ لأنها مقدّسة وتمثل حياة وإحياء للناس، وفي المبحث الأخير كانت تذرف الدموع لغياب الإلهة؛ فبكاء الشعراء على المرأة يعادل = بكاء إلهة الخصب / عشتار، فلم تكن المرأة من لحم ودم، لأن هذا البكاء كان يمثّل قرابين يتقرّب بها الشاعر للمرأة التي تعادل إلهة الخصب. أما الفصل الثالث فقد جاء بعنوان أسطورة العين الحيوانية والظواهر الطبيعية في الشعر الجاهلي، إذ قسمته إلى أربعة مباحث؛ جاء الأول بعنوان العين وشيم البرق والمطر، وقد تناولت فيه علاقة السحابة والمطر بالعين / عنانا، فهي (عنانا) وحدها تستطيع إنزال المطر وإسقاء الأرض الجرداء، وفي المبحث الثاني العين والبقرة الوحشية واقترانهما بالحور وحتحور، قد تكون صفة حور مأخوذة من حورس إله الزمن أو حتحور المتمثلة في رأس البقرة، وربطهما بحور العين في الجنة، أما المبحث الثالث تناولت فيه الحديث عن العين وزرقاء اليمامة وبكاء الحمام على ابنها ساق حر التي تشاكل بكاء عشتار على تموز، واقتراب زرقاء اليمامة بالحمامة من حيث اللغة والأسطورة، وتشابهما بأسطورة سمير أميس، والمبحث الأخير تحت عنوان العين والشمس؛ وذلك بإقامة علاقة وثيقة بين المرأة والشمس، وقد رأى البعض في رحلة المرأة صورة الشمس في رحلتها، وغيابها ممثلا بسرقة عين رع،وظهورها يعني استردادها، ومن بقايا تقديسها رمي سن الصبي المثغر للشمس؛ لأنها تمنح الحياة للأسنان الميتة. وهذه الدراسة لم يتطرق إليها أحد؛ لأنها تبحث عن أصول دلالات العين، وارتباطها بالدين الأسطورة وعودتها جميعها إلى عنانا / عشتار. وأنهيت بحثي بخاتمة اشتملت على أهم النتائج التي توصلت إليها في تلك الدراسة، واتبعتها بقائمة المصادر والمراجع مرتبة حسب الحروف الهجائية.
العين في الشعر الجاهلي/دراسة ميثولوجية